A biphasic growth model for cell pole elongation in mycobacteria - Mélanie T. M. Hannebelle (Nature Portfolio, 2020)
Mycobacteria grow by inserting new cell wall material at the cell poles. Here, Hannebelle et al. combine time-lapse optical and atomic force microscopy to show that single-cell growth is biphasic due to a lag phase of variable duration before the new pole transitions from slow to fast growth.